(untitled) (Research, Society and Development, 2020)
The mandarins have made possible a great increase in the production due to diverse cultural treatments, potentializing the increase of the production and reduction of the losses. However, studies are needed that can maintain post-harvest quality and increase in the field. Therefore, the objective of this work was to evaluate physically and chemically the ‘Dekopon’ tangerine fruits, analyzing the influence of the application of Calcium Chloride in 100, 200, 300, 400% of the recommended dosage, in addition to the control. The fruit samples were extracted from an experimental orchard in the municipality of Anápolis-GO and the analyzes were performed in the EMATER-GO laboratory. The experiment was conducted in a completely randomized design (CRD) composed of five doses of Calcium Chloride, three replicates during four weeks of evaluation (0, 7, 14 and 21 days), respectively, and the variables evaluated were submitted to polynomial regression analysis depending on the weeks. In this experiment were evaluated: loss of mass, coloration, soluble solids, titratable acidity and texture. The data originated from the analyzes were submitted to regression analysis by means of an F test at the probability level of 5%, to measure the meaning of the proposed model. It was concluded that the use of Calcium Chloride in most variables did not act positively in the post-harvest maintenance of fruit quality. However, it may be noted that desirable characteristics were observed in other post-harvest variables for applications of 100 and 200% of the recommended dosage during 21 days of evaluation.